As pesquisas “escolológicas” na obra de Helena Antipoff: proposta de uma ciência da escola (1929-1944) - Renata Silva Cruz (2024)
The aim of this work is to analyze the schoolological research conducted under the guidance of the Russian-Brazilian psychologist and educator Helena Antipoff (1892-1974) at the Psychology Laboratory of the Teacher Improvement School in Belo Horizonte, between 1929 and 1944. Schoolology is a neologism proposed by Antipoff to name a set of psychopedagogical and experimental studies that she implemented in the Improvement School with the aim of studying the school and everything related to it: school administration, building, school hygiene, teaching material, school regime, organization of classes, characteristics of teaching, teaching methods, various auxiliary institutions, and the child of school age itself. The proposal was to carry out systematic studies of school institutions based on empirical verifications of their functioning and the quality of teaching, aiming at the construction of a science of the school. One of the products of these researches were monographs written by the student-teachers the School that aimed to survey the reality of the Minas Gerais school system. The theoretical-methodological perspective uses the concepts of appropriation, reception, and circulation of scientific theories and practices in a transnational approach. This theory argues that when circulating in different contexts, theories and practices undergo processes of appropriation that can result in innovations and the elaboration of new knowledge questions. It is a qualitative research with a historiographical perspective that developed through a bibliographic research with documentary analysis. The results indicate that schoolology proposed a science of the school based on the foundations of child psychology, experimental pedagogy, and natural experimentation. Scientific theories, when circulating, undergo processes of transformation through which ideas gain meaning in the new context from the cultural experience and the demands from which they are appropriated and adapted. This study shows that schoolology played a significant role in transforming education research and teacher training process, by incorporating the principles of education sciences. In this context, we can understand that schoolological research is a response to the needs perceived by Antipoff about the reality of the Minas Gerais educational system, inspired by her previous experiences and the research developed throughout her work at the Improvement School.